Peran Kepemimpinan Transaksional Dalam Manajemen Talenta Era Digital Di Kabupaten Pekalongan - Dio Samudra; Fathan Aulia (E-Jurnal Kajen, 2025)
The role of transactional leadership in talent management in the digital era is becoming increasingly significant as businesses navigate a highly digitalized environment. Companies face the challenge of managing talent with an adaptive and technology-based approach. This study employs a literature review method by analyzing relevant international journals from the past five years to understand how transactional leadership can be effectively applied in modern human resource management. While transactional leadership is often criticized for being less flexible than transformational leadership, this study finds that key elements such as clarity of expectations, a measurable reward system, and active supervision remain highly relevant in the digital era. By leveraging technology and data analytics, transactional leadership can enhance work effectiveness, improve productivity, and ensure adherence to established standards. The findings indicate that, when implemented with a more flexible and data-driven approach, transactional leadership can serve as a strong foundation for digital talent management. Furthermore, this research contributes to a deeper understanding of how transactional leadership principles can be integrated with the needs of a dynamic modern workforce. It offers new perspectives for organizations in developing leadership strategies that align with the rapid evolution of the digital era, ultimately enriching management knowledge and advancing literacy in this field